PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN ETOS KERJA GURU TERHADAP KINERJA GURU SMA BUDDHIS BODHICITTA MEDAN - Simanungkalit, Josua Chariston; Telambanua, Eben H; Sihombing, Elsina (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
The problem of education quality is currently also being faced by schools in Medan City, especially private high schools. The issue of education must be of great concern because through educational institutions quality human resources can be created. The quality of human resources plays a major role in determining the success of activities in various physical and non-physical development sectors. In this research, the method used is a survey, while the type of research is correlational research. The survey method is used to obtain data from certain natural places, but researchers carry out treatments in collecting data, for example by distributing questionnaires, tests, structured interviews and so on. The survey was conducted on teachers at the Medan Bodhicitta Buddhist High School. This research technique was carried out to analyze the influence of two independent variables, namely the principal's leadership (X_1), work ethic (X_2), on one dependent variable, namely teacher performance (Y). There is no significant influence of the principal's leadership and teacher work ethic on teacher performance at Bodhicitta Buddhist High School. It can be seen that the value of F_count < F_table (3.008 < 3.340) with a significance level of 0.066 is greater than 0.05. There is no significant influence between the principal's leadership on teacher performance at Bodhicitta Buddhist High School. This can be seen from the t test between the principal's leadership and teacher performance, the calculation results show t_count < t_table, namely 1.951 < 2.048 at a significance level of 0.061 and N = 31. There is a significant influence of teacher work ethic on teacher performance at Bodhicitta Buddhist High School. This can be seen from the t test between teacher work ethic and teacher performance, the calculation results show t_count > t_table, namely 2.347 > 2.048 at a significance level of 0.026 and N = 31.